2013
DOI: 10.1159/000355972
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cellular Cytotoxicity in Patients on Chronic Hemodialysis

Abstract: Background: Antibody (Ab)-dependent cellular cytotoxicity (ADCC) is considered to be a relevant mechanism of action of Ab-based tumor therapies. However, knowledge about ADCC capacity of dialysis patients (DP) is limited. The aim of our study was to investigate if ADCC capacity of effector cells obtained from DP differed from those of healthy individuals (HI). Methods: First, we performed ADCC assays with isolated polymorphonuclear cells (PMN) and peripheral blood mononuclear cells (PBMC), mediated by the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although IgG2 Fc and IgG4 Fc fragments can be used for constructing the full-length antibody when Fc effector function is undesirable for therapeutic activity, they show decreased conformational stability relative to that of IgG1 because of their higher propensity to aggregate [74,75]. It has been observed that IgG2 Fc is not completely devoid of ADCC activity under certain conditions [76,77]. Besides, disulfide-bond reshuffling and Fab-arm exchange occurring in IgG2 and IgG4 subclasses lead to multiple heterogeneous isoforms with altered activities [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Although IgG2 Fc and IgG4 Fc fragments can be used for constructing the full-length antibody when Fc effector function is undesirable for therapeutic activity, they show decreased conformational stability relative to that of IgG1 because of their higher propensity to aggregate [74,75]. It has been observed that IgG2 Fc is not completely devoid of ADCC activity under certain conditions [76,77]. Besides, disulfide-bond reshuffling and Fab-arm exchange occurring in IgG2 and IgG4 subclasses lead to multiple heterogeneous isoforms with altered activities [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Notably, panitumumab is not effective at recruiting NK cells and inducing NK cell-mediated ADCC but is effective at recruiting ADCC by myeloid effector cells (i.e., neutrophils and monocytes). 46,47 Based on the importance of RAS status for stratifying patients for treatment with cetuximab, several studies have demonstrated that the specific RAS mutation also determines the responsiveness to panitumumab treatment. 48,49 Further data are still needed to clarify the role of each specific RAS mutation for anti-EGFR-based treatments in mCRC and other types of cancers and this information should be considered for further clinical uses.…”
Section: Panitumumabmentioning
confidence: 99%